2020
DOI: 10.15850/ijihs.v8n1.1911
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Indirect Immunofluorescence Assay Antinuclear Antibody in Pediatric Lupus Nephritis

Abstract: Objective: To determine the association between Anti-Nuclear Antibody (ANA) pattern in pediatric Systemic Lupus Erythematosus (SLE) patients and proteinuria as a sign of renal involvement in SLE. Methods: This was a cross-sectional study, using data from medical records involving 89 newly diagnosed with SLE (aged ≤ 18 years) in Department of Child Health Dr. Hasan Sadikin General Hospital, Bandung, from January 1st 2018 to June 30th 2019. Data of ANA pattern and proteinuria were collected from medical record.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Furthermore, both homogenous and speckled patterns were observed to have relatively high risk of lupus nephritis, although this was not statistically significant. Conversely, Novianti et al observed no significant correlation between ANA pattern and renal involvement, as indicated by proteinuria, in a group of 89 newly diagnosed, pediatric SLE patients [ 44 ]. Another intriguing case of a 34-year-old male was reported in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both homogenous and speckled patterns were observed to have relatively high risk of lupus nephritis, although this was not statistically significant. Conversely, Novianti et al observed no significant correlation between ANA pattern and renal involvement, as indicated by proteinuria, in a group of 89 newly diagnosed, pediatric SLE patients [ 44 ]. Another intriguing case of a 34-year-old male was reported in Japan.…”
Section: Discussionmentioning
confidence: 99%